Efektivitas dan Efisiensi Pengelolaan Anggaran Pembangunan Infrastukrut Pada Dinas PUTRPP Kabupaten Maros - Hajar; Syamsul Bakhtiar Ass; Nuraeni Nuraeni; Abdurrahman Hadi; Ummul Chair (Movere Journal, 2025)
The purpose of this study is to determine the effectiveness and efficiency of road infrastructure budget management at the Public Works, Spatial Planning, Land and Transportation Agency (PUTRPP) of Maros Regency. This study uses a quantitative research type with a descriptive approach. The data sources used are primary and secondary data in the form of financial reports and other important documents such as agency history and organizational structure that support this research. Data collection techniques use observation or observation and interviews. The analysis method uses the effectiveness and efficiency ratio formula. The results of the study show that in the last 5 years the management of the road infrastructure budget is in the very effective category with an average of 112.89% and a budget growth rate of -0.56%. Meanwhile, the efficiency ratio shows that in the last 5 years the management of the road infrastructure budget is in the very efficient category with an average of 4.45% and a budget growth rate of -13.3%.